2022
DOI: 10.1093/ofid/ofac200
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Infectious Diseases Consultation on the Outcome of Patients With Enterococcal Bacteremia: A Systematic Literature Review and Meta-analysis

Abstract: Background Enterococcal bacteremia carries significant mortality. While multiple studies have evaluated the impact of infectious disease consultation (IDC) on this condition, these studies were limited by the low numbers of patients enrolled. This systemic literature review and meta-analysis were conducted to determine whether IDC was associated with a mortality benefit among patients with enterococcal bacteremia. Methods We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Expert consultation could result in quicker selection of optimal antimicrobial therapy, increased likelihood of source identification and control (ie central line removal), improved mortality, and shortened length of hospital stay. [14][15][16][17] While not a replacement for infectious diseases consultation, ASP support does provide expert guidance on antimicrobial use. Our analysis showed that BCID use was still associated with decreased time to optimal therapy and time to deescalation of MRSA/PsA agents when ASP support was not available.…”
Section: Discussionmentioning
confidence: 99%
“…Expert consultation could result in quicker selection of optimal antimicrobial therapy, increased likelihood of source identification and control (ie central line removal), improved mortality, and shortened length of hospital stay. [14][15][16][17] While not a replacement for infectious diseases consultation, ASP support does provide expert guidance on antimicrobial use. Our analysis showed that BCID use was still associated with decreased time to optimal therapy and time to deescalation of MRSA/PsA agents when ASP support was not available.…”
Section: Discussionmentioning
confidence: 99%
“…Consultations with infectious disease (ID) or other specialists have been performed when ought to be necessary. In other fields such as blood stream infection with Staphylococcus aureus, enterococcal bacteriemia or candidemia ID, specialist consultation has been demonstrated to reduce mortality risk significantly [23][24][25]. This may explain minor differences before and after implementation of the MDT infection board.…”
Section: Discussionmentioning
confidence: 99%